Pengaruh Kebijakan Legislatif dalam Upaya Menanggulangi Tindak Pidana Korupsi di Indonesia - Efraim Abigail Bukit; Yasmirah Mandasari Saragih; Fauzan Fauzan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Corruption is a multidimensional challenge that hampers economic, social and political development in Indonesia. Legislative policy plays a key role in efforts to overcome criminal acts of corruption, by providing a legal framework that becomes the basis for law enforcement. This research aims to analyze the influence of legislative policies in tackling criminal acts of corruption in Indonesia, evaluate obstacles in their implementation, and identify strategies to increase their effectiveness. This research uses a qualitative approach with a literature review method, examining various legal documents, reports from related institutions, and academic literature. The research results show that legislative policies, such as Law no. 31 of 1999 jo. Law no. 20 of 2001 concerning the Eradication of Corruption Crimes, played a significant role in establishing anti-corruption institutions, such as the Corruption Eradication Commission (KPK), and provided a strong legal basis for law enforcement. However, the effectiveness of this policy faces obstacles in the form of systemic corruption, political resistance, weak inter-institutional coordination, and policy revisions that weaken the independence of anti-corruption institutions. This research also found that transparency in the legislative process, strengthening the monitoring system, and increasing community participation are strategic steps to support anti-corruption policies. This research concludes that the success of legislative policies in eradicating corruption depends on strong political commitment, the integrity of law enforcement, and active community participation. By overcoming existing obstacles, legislative policies can become a more effective instrument in realizing clean and transparent governance.